Mycoses in children - Ginter, G... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1998)
Report of experiences in treating childhood onychomycosis (caused by Trichophyton rubrum) in 12 children. Treatment with itraconazole 200 mg once daily for 12 weeks, revealed clinical and mycological cure in 10 children within 2-4 months. In one child no cure could be obtained, another one failed to appear for the follow-up. In 31 children with tinea capitis caused by Microsporum canis (microsporosis) systemic oral treatment was performed using itraconazole. The drug was administered as a solution once daily with a meal, in a dosage of 5 mg/kg bodyweight. In all 31 children with an average of 5,7 years, cure could be obtained in 6,1 weeks (standard aberration about 2 weeks). In conclusion, systemic treatment with oral antifungals is effective and safe in childhood onychomycosis and tinea capitis. In our experience the azoles seem to be the drug of choice in the management of scalp infection due to microsporum canis in children. Side effects using itraconazole were mild and transient.
Keywords: Administration, oral; Child; Drug therapy; Itraconazole; Microsporum; Onychomycosis; Tinea capitis; Treatment outcome